2012
DOI: 10.1128/jvi.02005-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Antagonism between the Y181C and E138K Mutations in HIV-1 Reverse Transcriptase

Abstract: Etravirine (ETR) is an expanded-spectrum nonnucleoside reverse transcriptase inhibitor (NNRTI) approved for use as an antiretroviral agent in treatment-experienced patients. Y181C and E138K in HIV-1 RT are among 20 different drug resistance mutations associated with ETR. However, E138K can be consistently selected by ETR when wild-type viruses but not viruses containing Y181C are grown in tissue culture. This study was carried out to evaluate any possible mechanisms that might explain antagonism between the Y1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…We have recently shown that E138K consistently emerges in CBMCs under ETR selection pressure but not in MT2 cells that have larger dNTP pools (37,48). We now also demonstrate that the addition of N348I to E138K further decreased viral replication in both cell types and that the addition of M184V to the E138K/ N348I double mutant slightly increased viral replication capacity compared to E138K/N348I alone.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We have recently shown that E138K consistently emerges in CBMCs under ETR selection pressure but not in MT2 cells that have larger dNTP pools (37,48). We now also demonstrate that the addition of N348I to E138K further decreased viral replication in both cell types and that the addition of M184V to the E138K/ N348I double mutant slightly increased viral replication capacity compared to E138K/N348I alone.…”
Section: Discussionsupporting
confidence: 55%
“…One reason for this may be that the patients who received ETR were almost all treatment experienced and harbored the N348I substitution that, either alone or in combination with M184V, can prevent or delay the emergence of E138K under ETR and RPV drug pressure, as shown here. It is notable that Y181C is also antagonistic with E138K and can prevent the emergence of E138K in cell culture under ETR or RPV pressure (38,48,61). Y181C was present in the DUET studies conducted on the efficiency of ETR in treatmentexperienced subjects in 32% of patients at baseline (90); this explains the low prevalence of E138K in these trials.…”
Section: Discussionmentioning
confidence: 99%
“…We also wished to provide mechanistic insight into reasons for the favored selection of E138K versus other E138 mutations in the ECHO and THRIVE clinical studies. E138V was also chosen for study because it had been observed in patients who failed ETR-containing therapy in the DUET studies (23) and in cell culture under ETR pressure (34,35) and has not previously been characterized.…”
mentioning
confidence: 99%
“…Recently, deep sequencing analysis of patients who suffered from RPV virologic failure in the phase III studies ECHO and THRIVE showed that K101E and E138K rarely occurred on the same genome (65). However, no natural antagonism seems to exist between K101E and E138K; thus, the occurrence of other mutational pairs associated with NNRTI resistance, such as Y181C and E138K, may be in part a matter of chance in the context of RT enzymes that are functional and commensurate with viral replication capacity (55). In conclusion, enzymatic and cell-based assays show that K101E can play a significant role in resistance to RPV.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, antagonism seems to exist between E138K and Y181C, and the mechanisms involved have been reported (54,55). In the present study, we have compared the effects of the K101E and E138K substitutions on drug susceptibility using the Monogram PhenoSense HIV RT assay.…”
Section: Discussionmentioning
confidence: 99%